Hubungan Dukungan Keluarga dan Tingkat Pengetahuan Lansia terhadap Keaktifan dalam mengikuti Kegiatan Posyandu Lansia di Posyandu Apel RW. 16 Harapan Baru Bekasi - Ina Rahmawati; Isnaeni Isnaeni (Malahayati Nursing Journal, 2023)
ABSTRACT According to WHO in 2021 in Southeast Asia the elderly population is around 142 million people (8%). The Central Statistics Agency for 2022 reports that the percentage of the elderly population in Indonesia is 10.48%. Along with the increasing elderly population, the government has formulated various policies for elderly health services such as the Elderly Posyandu. Elderly Posyandu is a form of participation of the elderly community in efforts in the health sector to achieve optimal health status and healthy and independent aging conditions. Objective to determine the relationship between family support and the level of knowledge of the elderly on activeness in participating in elderly posyandu activities. Methods analytic with cross sectional approach. The sample in this study were some of the elderly who were enrolled in Posyandu Apel as many as 86people. The sampling technique uses systematic random sampling. The distribution of the frequency of activity in posyandu was mostly active (72.1%), received support from family (76.7%) and sufficient knowledge (55.8%). There is a relationship between family support and knowledge of active participation in elderly Posyandu activities (p value 0.005). There is a relationship between family support and knowledge of being active in participating in elderly posyandu activities. It is hoped that the elderly will be more active in participating in the activities of the elderly Posyandu so that they can better understand, understand and want to take advantage of the Posyandu in improving their health status independently. Keywords: Family support, Knowledge, Posyandu for the Elderly  ABSTRAK WHO menyatakan tahun 2021 di Asia Tenggara populasi Lansia sekitar 142 juta jiwa (8%). Badan Pusat Statistik tahun 2022 melaporkan, persentase penduduk lansia di Indonesia sebesar 10,48%. Seiring dengan semakin meningkatnya populasi lansia, pemerintah telah merumuskan berbagai kebijakan pelayanan kesehatan usia lanjut seperti Posyandu Lansia. Posyandu lansia merupakan bentuk peran serta masyarakat lansia dalam upaya bidang kesehatan untuk mencapai derajat kesehatan yang optimal serta kondisi menua yang sehat dan mandiri. Tujuan penelitian untuk mengetahui hubungan dukungan keluarga dan tingkat pengetahuan lansia terhadap keaktifan dalam mengikuti kegiatan posyandu lansia. Metode penelitian analitik dengan pendekatan cross sectional. Sampel dalam penelitian ini adalah sebagian lansia yang terdaftar di Posyandu Apel sebanyak 86 orang. Teknik pengambilan sampel menggunakan systematic random sampling. Distribusi frekuensi keaktifan mengikuti posyandu sebagian besar aktif (72,1%), mendapat dukungan dari keluarga (76,7%) dan pengetahuan cukup (55,8%). Ada hubungan dukungan keluarga dan pengetahuan terhadap keaktifan dalam mengikuti kegiatan posyandu lansia (nilai p value 0.005). Ada hubungan dukungan keluarga dan pengetahuan terhadap keaktifan dalam mengikuti kegiatan posyandu lansia. Diharapkan lansia lebih aktif dalam mengikuti kegiatan posyandu lansia sehingga dapat lebih mengerti, memahami dan mau memanfaatkan posyandu dalam meningkatkan derajat kesehatan secara mandiri. Kata Kunci : Dukungan Keluarga, Pengetahuan, Posyandu Lansia